ANALISIS KINERJA PEMBANGUNAN DIMENSI INFRASTRUKTUR DAN PELAYANAN PUBLIK DI PROVINSI NUSA TENGGARA BARAT - Wahyunadi Wahyunadi; Mansur Afifi; Muaidy Yasin (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
This research is entitled Performance Analysis of Infrastructure and Public Service Dimensions in West Nusa Tenggara Province. This research is a type of verification research, the data collection process is carried out by compiling a matrix of the required variables according to the analysis model. The results show that based on the available data, the results of the calculation of performance indicators for regency / municipal governments in the province of West Nusa Tenggara through the regional development index measurement model, that infrastructure development and macroeconomic development should have a reciprocal relationship, because infrastructure development leads to economic expansion through a multiplier effect. . Meanwhile, economic expansion creates the need to expand existing infrastructure, to absorb the increasing flow of goods and people circulating or circulating throughout the economy.